N-type Mg3Sb2-xBix with improved thermal stability for thermoelectric power generation. (December 2020) - Shang, Hongjing; Liang, Zhongxin; Xu, Congcong; Song, Shaowei; Huang, Daxing; Gu, Hongwei; Mao, Jun; Ren, Zhifeng; Ding, Fazhu
Abstract: The recently discovered n-type Mg3 Sb2- x Bi x alloys with high thermoelectric performance hold great potential for applications in waste heat recovery due to their high average zT in the temperature range between 300 and 773 K. However, systematic studies of their thermal stability remain lacking and are significant for these thermoelectric materials since the possible degradation of their thermoelectric performance could greatly limit their practical applications. Here we studied the thermal stability of the Mg3 Sb2- x Bi x alloys via in situ measurements of their thermoelectric properties at different temperatures, along with microstructural and composition characterizations. Our results show that Mg3 Sb2- x Bi x alloys are unstable when the temperature is above 673 K due to significant Mg loss and changed microstructures. By coating Mg3 Sb2- x Bi x alloys with boron nitride, the Mg loss can be effectively suppressed, thus greatly improving their thermal stability. Additionally, energy conversion efficiency measurements validated the high thermoelectric performance of the Mg3 Sb2- x Bi x alloys and further confirmed the improved thermal stability of the boron-nitride-coated sample. Therefore, our study provides an effective strategy for improving the thermal stability of Mg3 Sb2- x Bi x, thus promoting it as a promising candidate for thermoelectric power generation. Graphical abstract: Image, graphical abstract